எங்கள் ஆசிரியர்களுடன் 1-ஆன்-1 ஆலோசனை நேரத்தைப் பெறுங்கள். டாப்பர் ஆவதற்கு நாங்கள் பயிற்சி அளிப்போம்

Book Free Demo
Identity \(- 4\): (a + b)(a − b)= a2b2
Let us first, simplify the identity (a + b)(a − b)= a2b2.
Multiply the expression, as shown below.
pic 1.png
Now, we construct a figure to understand the concept.
pic 3.png
Then we construct a rectangle using the above information.
In the given figure, \(AB = AD = a\).

So, the area of square \(ABCD = a^2\).
pic 2.png
Also, \(SB = DP = b\). Then the area of the rectangle \(SBCT = ab\).
Similarly, the area of the rectangle \(DPRC = ab\). And the area of the square \(TQRC = b^2\).
Area of the rectangle \(DPQT = ab − b^2\).
Hence, \(\text{the area of the rectangle APQS = The area of square ABCD}\) \(\text{– area of rectangle STCB}\) \(\text{+ area of rectangle DPQT}\).
Therefore, (a + b)(a − b)= a2b2.
Simplify (5x + 7)(5x  7) using the identity.
First, develop the given (5x + 7)(5x  7) expression using the identity (a + b)(a − b)= a2b2.
Here, \(a = 5x\); \(b = 7y\).
(5x + 7)(5x7)=(5x)2(7)2=52×x2(7)2=25x249
Therefore, (5x + 7)(5x  7) \(=\) 25\(x^2 -\)49.